Effects of Air Frying on French Fries: The Indication Role of Physicochemical Properties on the Formation of Maillard Hazards, and the Changes of Starch Digestibility - Dong, Lu; Qiu, Cai-yi; Wang, Rui-can; Zhang, Yan; Wang, Jin; Liu, Jing-min; Yu, Hua-ning; Wang, Shuo (Frontiers in Nutrition, 2022)
This study focused on the formation of Maillard hazards in air fried fries, highlighting the correlation between the resultant physical properties of the fries and the formation of Maillard hazards. In the meantime, the effects of air frying on the in vitro starch digestibility of fries were explored. Potato strips were fried at various temperatures (180-200°C) and time (12-24 min). Results indicated that the extent of browning, hardness, and the contents of Maillard hazards (acrylamide, 5-hydroxymethylfurfural, methylglyoxal, and glyoxal) all increased steadily with air frying temperature and time. Moisture content were negatively correlated (p <0.001) with Maillard hazards content and physicochemical properties except for L* with the correlation coefficients range from -0.53 to 0.94, and positively correlated with L* value with correlation coefficient was 0.91, hence, reducing the Maillard hazard exposure while maintaining the desired product quality can be achieved by controlling the moisture content of the air fried French fries. Compared with deep frying (180°C-6 min), air frying decreased acrylamide and 5-hydroxymethylfurfural content with the maximum reduction rate were 47.31% and 57.04%, respectively. In addition, the in vitro digestion results suggested that air frying resulted in higher levels of slowly digestible starch (48.54%-58.42%) and lower levels of resistant starch (20.08%-29.34%) as compared to those from deep frying (45.59% ± 4.89% and 35.22% ± 0.65%, respectively), which might contribute to more balanced blood sugar levels after consumption. Based on the above results, it was concluded that air frying can reduce the formation of food hazards and was relatively healthier.